Flipping the switch on some of the slowest mutating genomes: Direct measurements of plant mitochondrial and plastid mutation rates in msh1 mutants. - Amanda K Broz; Mychaela M Hodous; Yi Zou; Patricia C Vail; Zhiqiang Wu; Daniel B Sloan (PLoS Genetics)
Plant mitochondrial and plastid genomes have exceptionally slow rates of sequence evolution, and recent work has identified an unusual member of the MutS gene family ("plant MSH1") as being instrumental in preventing point mutations in these genomes. However, the effects of disrupting MSH1-mediated DNA repair on "germline" mutation rates have not been quantified. Here, we used Arabidopsis thaliana mutation accumulation (MA) lines to measure mutation rates in msh1 mutants and matched wild type (WT) controls. We detected 124 single nucleotide variants (SNVs: 49 mitochondrial and 75 plastid) and 668 small insertions and deletions (indels: 258 mitochondrial and 410 plastid) in msh1 MA lines at a heteroplasmic frequency of ≥ 20%. In striking contrast, we did not find any organelle mutations in the WT MA lines above this threshold, and reanalysis of data from a much larger WT MA experiment also failed to detect any variants. The observed number of SNVs in the msh1 MA lines corresponds to estimated mutation rates of 6.1 × 10-7 and 3.2 × 10-6 per bp per generation in mitochondrial and plastid genomes, respectively. These rates exceed those of species known to have very high mitochondrial mutation rates (e.g., nematodes and fruit flies) by an order of magnitude or more and are on par with estimated rates in humans despite the generation times of A. thaliana being nearly 100-fold shorter. Therefore, disruption of a single plant-specific genetic factor in A. thaliana is sufficient to erase or even reverse the enormous difference in organelle mutation rates between plants and animals.